2009
DOI: 10.1149/1.3142365
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Corrosion Layers Electrochemically Formed on the Lead–Silver/H[sub 2]SO[sub 4]+Mn(II) Interface

Abstract: The corrosion layers electrochemically formed on the lead–silver/ normalH2SO4+Mn(II) interface were studied through open-circuit potential monitoring, cyclic voltammetry, and chronoamperometry and were characterized by cyclic voltammetry, X-ray diffraction, and scanning electron microscope coupled to an energy dispersive spectrometer to analyze microregions. Mn(II) oxidation reactions take place in the range of 1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…We may thereby conclude that after an hour of electrolysis, electrocatalytic properties of MnO 2 anodic layers have diminished and tend to be equal in both scan directions. On comparing the charges obtained, the ACZn12Mn system exhibits higher values for O2 process, which may be related to simultaneous reactions occurring in this system, already described by several authors (Chen and Dutrizac, 2011;Liu et al, 2011;Masatsugu, 2011;Recéndiz et al, 2008Recéndiz et al, , 2009Recéndiz et al, , 2010Schmachtel et al, 2008;Tjandrawan and Nicol, 2013;Zhang and Hua, 2009). Fig.…”
Section: Electrodesupporting
confidence: 66%
See 3 more Smart Citations
“…We may thereby conclude that after an hour of electrolysis, electrocatalytic properties of MnO 2 anodic layers have diminished and tend to be equal in both scan directions. On comparing the charges obtained, the ACZn12Mn system exhibits higher values for O2 process, which may be related to simultaneous reactions occurring in this system, already described by several authors (Chen and Dutrizac, 2011;Liu et al, 2011;Masatsugu, 2011;Recéndiz et al, 2008Recéndiz et al, , 2009Recéndiz et al, , 2010Schmachtel et al, 2008;Tjandrawan and Nicol, 2013;Zhang and Hua, 2009). Fig.…”
Section: Electrodesupporting
confidence: 66%
“…It is important to say that this catalytic effect is observed in the first 10 min of oxidation, but after 1 h it tends to inhibit itself. On other hand, α-MnO 2 was identified by XRD studies and reported by Recéndiz et al (2009) in tests carried out at 180 g/L H 2 SO 4 and Mn(II) without Zn 2+ ions. Despite this evidence, XRD studies are necessary in order to confirm the presence of α-MnO 2 .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In the forward scan direction, the surface is covered mostly with PbO and PbSO 4 , which are non-conductive phases, whereas in the reverse direction the surface is covered by the semi-conductive PbO 2 phase facilitating the OER. 49 The difference in current densities in the forward and reverse scan directions was more pronounced when the MnO 2 fraction was increased in the anodes. At 1.9 V Ag/AgCl , for example, this difference for the Pb-20MnO 2 is three times that of the Pb-5MnO 2 .…”
Section: Resultsmentioning
confidence: 97%